Evaluation of the effectiveness of the prepectoral breast reconstruction with Braxon dermal matrix: First multicenter European report on 100 cases. Issue 6 (8th May 2017) - Vidya, Raghavan; Masià, Jaume; Cawthorn, Simon; Berna, Giorgio; Bozza, Fernando; Gardetto, Alexander; Kołacińska, Agnieszka; Dell'Antonia, Francesco; Tiengo, Cesare; Bassetto, Franco; Caputo, Glenda G.; Governa, Maurizio
Abstract: We report the outcomes of the European prospective study on prepectoral breast reconstruction using preshaped acellular dermal matrix for complete breast implant coverage. Seventy‐nine patients were enrolled between April 2014 and August 2015 all over Europe using a single protocol for patient selection and surgical procedure, according to the Association of Breast Surgery and British Association of Plastic Reconstructive and Aesthetic Surgeons joint guidelines for the use of acellular dermal matrix in breast surgery. The preshaped matrix completely wraps the breast implant, which is placed above the pectoralis major, without detaching the muscle. A total of 100 prepectoral breast reconstructions with complete implant coverage were performed. This series, with mean follow‐up of 17.9 months, had two cases of implant loss (2.0%) including one necrosis of the nipple and one wound breakdown (1.0% respectively). No implant rotations were observed. Good cosmetic outcomes were obtained with natural movement of the breasts and softness to the touch; none of the patients reported experiencing pain or reduction in the movements of the pectoralis major muscle postoperatively. The use of preshaped acellular dermal matrix for a complete breast implant coverage in selected patients is safe and gives satisfactory results, both from the aesthetic view point and the low postoperative complication rates. Further studies reporting long‐term outcomes are planned.